PWE-148 Hepatotoxicity From Anabolic Androgenic Steroids Marketed as Dietary Supplements: Contribution from Atp8B1/Abcb11 Mutations?. (4th June 2013) - Elsherrif, Y; Potts, J R; Howard, M R; Barnardo, A; Cairns, S; Knisely, A S; Verma, S
Abstract : Introduction: In the United Kingdom (UK) it is illegal to produce, supply, or possess androgenic anabolic steroids (AAS) with intent. Despite this, non-prescription use of AAS, often marketed as dietary supplements, persists. We encountered drug-induced liver injury (DILI) associated with use of AAS and attempted to elucidate underlying mechanisms. Methods: We describe two patients with cholestatic DILI following ingestion of the dietary supplement massdrol ("Celtic Dragon") containing the AAS 2a-17a-dimethyl-etiocholan-3-one, 17b-ol. Results: Two Western European males (aged 25 and 45 years) presented to our institute between July, 2011, and March, 2012, with jaundice and intractable pruritus following use of massdrol acquired from fellow gym users. Screening found no other causes of hepatobiliary disease. Despite significant hyperbilirubinaemia (respective peaks: 614 and 229 µmol/L), peak gamma glutamyl transferase activities were within "normal range". Besides "bland" intralobular cholestasis, consistent with DILI, liver biopsy in both found deficiency of canalicular expression of the ectoenzymes neutral endopeptidase (CD10), alanyl aminopeptidase (CD13), GGT, and carcinoembryonic antigen (CD66). This suggested generalised abnormality in ectoenzyme trafficking to, or retention within, canalicular membranes, as seen in ATP8B1 disease (familial intrahepatic cholestasis 1 [FIC1]). The younger patient showed normal expression of bile salt export pump (BSEP, encoded by ABCB11 ) and of multidrug resistance protein 3 (MDR3; encoded by ABCB4 ); in the older BSEP but not MDR3 marking was focally diminished. While this may have been due to AAS-induced inhibition of expression of normal ATP8B1 / ABCB11, it also raised the intriguing possibility of mutation in either of these genes – in effect, that AAS exposure had triggered initial episodes of benign recurrent intrahepatic cholestasis type 1/2. On sequencing, ATP8B1 was normal in both patients; the younger was heterozygous for the mutation c.2093G > A mutation in ABCB11, a known polymorphism previously encountered in association with intrahepatic cholestasis following antibiotic exposure (personal communication, R Thompson). Morbidity from cholestasis and pruritus was substantial, necessitating use of multiple antipruritic agents and consideration for extracorporal albumin dialysis ( MARS ). At last follow-up, however, jaundice was resolved in both. Conclusion: AAS marketed as dietary supplements remain a cause of serious DILI in the UK; underlying mechanisms remain speculative but may include unmasking of genetic cholestatic syndromes. Disclosure of Interest: None Declared.